The Influence of Information Technology, Service Quality, and Taxpayer Awareness on the Compliance of Property Taxpayer PBB-P2 UPTD Kuta Utara, Badung Regency - tarini, Ni Luh Putu Eddy Tarini; Ida Ayu Putu Sri Widnyani; Gede Wirata (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
One important step to increase taxpayer compliance with land and building taxes is to pay attention to the factors that influence it, namely information technology, service quality and taxpayer awareness. Based on this, the problem that can be formulated in this research is whether information technology, service quality and taxpayer awareness influence Taxpayer Compliance PBB-P2 UPTD North Kuta Badung Regency.Data collection in this research was carried out by means of documentation, observation, interviews and questionnaires with 100 taxpayers. The collected questionnaires were then analyzed using the Structure Equation Model (SEM) Amos version 22. Based on the calculation results, it was concluded that information technology had a positive and significant influence on PBB-P2 UPTD North Kuta Badung Regency. Service quality has a positive and significant influence on PBB-P2 UPTD North Kuta Badung Regency. Taxpayer awareness has a positive and significant influence on PBB-P2 UPTD North Kuta Badung Regency.